PEDAGOGICAL PROBLEMS OF PROFESSIONAL FORMATION COMPETENCIES OF FUTURE TEACHERS - Leszek Frederick Kozhenevsky (Academy of Cognitive and Natural Sciences, 2008)
In article pedagogic problems of formation of professional competence of the future teachers are considered.